Discussion on Protein Metabolism and Requirement of Aerobics Athletes during Training Based on Multisensor Data Fusion - Gong, Hua; Chen, Shuang; Yu, Shuo; Liu, Dong; Li, Xin; Shan, Zeliang; Kong, Fan; Yan, Zhi; Han, Feng (Journal of healthcare engineering, 2022)
Competitive aerobics has emerged as a highly competitive sport beyond its own physical limit. Modern competitive aerobics competition is very fierce; athletes cannot only rely on a specific competitive skill to achieve good results. Protein is the physical basis of life activity. The life activity of human body is closely related to protein, and protein is closely related to human exercise ability. This article aims to study protein metabolism and demand of aerobics athletes during training based on multisensor data fusion. A total of 26 female aerobics athletes were randomly divided into two groups: exercise group and exercise + nutrition group. According to the characteristics of human motion, a comprehensive measurement acquisition sensor system for collecting human motion information is designed and implemented, and the system is used to monitor the subject’s protein condition in real time. The subjects took protein nutrient solution before breakfast every day. The dynamic recognition algorithm designed in this paper also has shortcomings, and the monitoring protein method based on gait and other signs is not completely correct. The experiment lasted for 7 weeks. The results showed that the level of serum transferrin receptor decreased significantly in the quiet + nutrition group for 4 weeks, which was significantly different from that at 0 and 3 weeks in the same group (P < 0.01) and was significantly different from that in the same group at 7 weeks (P < 0.05). In the exercise group, the level of serum transferrin receptor increased significantly at 5 weeks, compared with the same group at 0 and 3 weeks (P < 0.05).